C/D box snoRNA SNORD113-6/AF357425 plays a dual role in integrin signalling and arterial fibroblast function via pre-mRNA processing and 2′O-ribose methylation. Issue 7 (21st October 2021) - van Ingen, Eva; van den Homberg, Daphne A L; van der Bent, M Leontien; Mei, Hailiang; Papac-Milicevic, Nikolina; Kremer, Veerle; Boon, Reinier A; Quax, Paul H A; Wojta, Johann; Nossent, A Yaël
Abstract: We have previously shown that C/D box small nucleolar RNAs (snoRNAs) transcribed from the DLK1-DIO3 locus on human chromosome 14 (14q32) are associated with cardiovascular disease. DLK1-DIO3 snoRNAs are 'orphan snoRNAs' that have no known targets. We aimed to identify RNA targets and elucidate the mechanism-of-action of human SNORD113-6 (AF357425 in mice). As AF357425-knockout cells were non-viable, we induced overexpression or inhibition of AF357425 in primary murine fibroblasts and performed RNA-Seq. We identified several pre-mRNAs with conserved AF357425/SNORD113-6 D′-seed binding sites in the last exon/3′ untranslated region (3′UTR), which directed pre-mRNA processing and splice-variant-specific protein expression. We also pulled down the snoRNA-associated methyltransferase fibrillarin from AF357425-High versus AF357425-Low fibroblast lysates, followed by RNA isolation, ribosomal RNA depletion and RNA-Seq. Identifying mostly mRNAs, we subjected these to PANTHER pathway analysis and observed enrichment for genes in the integrin pathway. We confirmed 2′O-ribose methylation in six integrin pathway mRNAs ( MAP2K1, ITGB3, ITGA7, PARVB, NTN4 and FLNB ). Methylation and mRNA expressions were decreased while mRNA degradation was increased under AF357425/SNORD113-6 inhibition in both murine and human primary fibroblasts, but effects on protein expression were more ambiguous. Integrin signalling is crucial for cell–cell and cell–matrix interactions, and correspondingly, we observed altered human primary arterial fibroblast function upon SNORD113-6 inhibition.